Conducting polymers synthesized by γ-radiolysis in very acidic aqueous medium. (June 2019) - Cui, Zhenpeng; Bahry, Teseer; Dazzi, Alexandre; Bui, Thanh-Tuân; Goubard, Fabrice; Remita, Samy
Abstract: In this work, conducting polymers were synthesized for the first time in acidic aqueous solutions by means of γ-irradiation. Poly(3, 4-ethylenedioxythiophene) (PEDOT) polymers were prepared under N2 O atmosphere in the presence of highly concentrated hydrochloric acid (HCl) at pH ~ 0, thanks to the oxidation of 3, 4-ethylenedioxythiophene (EDOT) monomers by Cl2 - oxidizing radicals produced in the medium by water radiolysis. UV–Vis absorption spectroscopy was used to estimate the radiolytic yield of EDOT oxidation as well as the required dose for quantitative PEDOT preparation. After a 72-kGy irradiation, PEDOT polymers, which form dark blue suspensions, were characterized by a large absorption band at around 700 nm. Size exclusion chromatography demonstrated that these radiosynthesized PEDOT polymers contain up to 20 EDOT units. After deposition, ATR-FTIR spectroscopy and Energy-Dispersive X-ray (EDX) analysis highlighted the doping of PEDOT polymers prepared in the presence of HCl. The morphology of radiosynthesized PEDOT polymers was characterized by SEM microscopy and by high-resolution AFM-IR microscopy coupled with infrared nanospectroscopy. Aggregated spheroidal PEDOT particles with diameters comprised between 200 and 500 nm were detected. In addition, cyclic voltammetry (CV) and four-point probe measurements demonstrated that PEDOT polymers radiosynthesized in very acidic medium are characterized by prominent electronic properties (small band gap and considerable electrical conductivity). Promisingly, the present radiolytic study should offer a new synthetic approach for the preparation in acidic aqueous media of conducting polymers with enhanced properties. Graphical abstract: fx1 Highlights: Radiolysis is used for conducting polymers synthesis in very acidic aqueous medium. Doped PEDOT polymers are produced in presence of HCl and HClO4 at pH = 0. Chemical, structural and morphological characterizations of PEDOT polymers are made. Their optical and electrical properties are compared to those got in neutral media. This is a new method for preparation of conducting polymers with enhanced properties.